Preprints: Accelerating Scholarly Communications - Ahmad, Umar Salisu (My University, 2022)
Slide deck of my presentation during #BioRTCNig2022 at Biomedical Science Research and Training Centre (BioRTC), where I talked about #preprints and open science and how they accelerate scholarly communications. I specifically discussed about an existing African preprints server, AfricArxiv, where our scientists and #researchers could share their research work freely and be digitalised using #doi assignments.
Keywords: Open Science; AfricArxiv; Scholarly communication